Local delivery of hyaluronic acid as an adjunct to scaling and root planing in the treatment of chronic periodontitis in smokers and non-smokers: A clinical and microbiological study - Mayuri Vajawat; Deepika Pawar Chandrashekara Rao; G S Vijay Kumar; Kempireddygaripalli Gangulappa Rajeshwari; Manohar Sharma Hareesha (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of the study is to assess the effects of adjunctive use of hyaluronic acid (HA), clinically and microbiologically in smokers and nonsmokers, in the management of chronic periodontitis. Material and Methods: 48 sites from 24 chronic periodontitis patients, including smokers and nonsmokers with probing depth >5 mm, were selected for the study. A split-mouth design was followed. Scaling and root planing (SRP) was performed for all the patients. The test sites received 0.8% HA gel whereas the control site received placebo gel. The clinical parameters plaque, gingival and bleeding indices, Pocket Probing Depth (PPD), and clinical attachment level (CAL) were evaluated at baseline, 1 and 3 months. Microbiological parameters were evaluated at baseline and 1 month. Results: The results showed reduction in PPD and gain in CAL in both smokers and nonsmokers at the end of 3rd month. The improvements in the test sites were statistically significant when compared with that of control sites. The microbiological analysis showed a significant reduction in Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis at the test sites when compared to the controls in both the groups. Conclusion: The findings in both groups suggest that the use of locally delivered 0.8% HA gel may be valuable as an adjunct to SRP in the treatment of chronic periodontitis.